Learning to adapt & adapting to learn - Using elements of outcome mapp ing in the ‘Resilient Adolescents in the Syria Crisis’ programme - Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were us ed by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. T he paper first outlines how the spheres of influence framework has bee n applied to develop an actor focused theory of change. It then descri bes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realist ic and practical results framework. The paper then continues to elabor ate how outcome journals, qualitative data analysis techniques and reg ular review meetings and reflection workshops were utilised for data c ollection, for collective learning among programme stakeholders and fo r informing planning and programme adjustment. Various practical guide lines and tips on how to implement elements of outcome mapping are pro vided. The final part of the paper explores to what extent outcome map ping was able to foster several key enablers of adaptive programme man agement and highlights some of the challenges that programme stakehold ers faced. Practical recommendations towards the use of outcome mappin g in future programmes are also proposed.